Call the police immediately: Factors influencing perpetrator arrest time in child abduction cases in South Korea. (March 2019) - Park, Jisun; Cho, Joon Tag
Abstract: Background: Considering the devastating long-term effects on victims caused by child abduction, a thorough examination of child abduction cases as well as the identification of specific factors determining offender arrest times are required. Objective: The current study aims to better understand the characteristics of child abduction and contribute to improving efficient investigation and rapid offender apprehension. Participants and setting: The study uses data from investigation and trial records of abduction cases in South Korea from 1997 to 2008. A total of 144 cases of child abductions were analyzed. We investigated the characteristics of victims and offenders and incident characteristics including crime planning, the use of violence, and the time taken to realize that a child was missing, reporting it to the police, and arresting perpetrators. Methods: We examined the data by using logistic regression analysis and the gamma generalized linear model. Results: It took significantly less time to arrest offenders if they had criminal records. The higher the age of the victim, the longer it took for the offender to be arrested. It took longer for the offender to be arrested in parental abduction cases than in non-parental abduction cases, and it took longer to arrest the perpetrator with delayed recognition that a child was missing and delayed police reporting. Conclusions: The current findings emphasize the importance of rapid responses following abductions. The study provides strategies to assist with accurate decision making by investigators and fast case resolution through the early arrest of child abductors.